Advances in the type IX secretion system: an exploration focusing on Riemerella anatipestifer - Pengfei Niu; Rong Guo; Chan Ding; Shengqing Yu (Current Research in Microbial Sciences)
The type IX secretion system (T9SS) is specific to the Fibrobacteres-Chlorobi-Bacteroidetes superphylum, the members of which have many specialized features, including gliding motility and the transport of cargo proteins across the outer membrane. At least 20 proteins have been identified as the components of T9SS. Proteins secreted by T9SS use the Sec system to cross the inner membrane, and the conserved C-terminal domain targets them to the T9SS for delivery to the extracellular environment or attachment to the outer membrane. Riemerella anatipestifer is an important pathogen of waterfowl, causing septicemic and exudative diseases. A genetic analysis recently detected T9SS in R. anatipestifer, in which it transports proteins and affects virulence. Moreover, at least 19 T9SS-transported proteins in R. anatipestifer strain Yb2 were identified, with multiple functions and affecting R. anatipestifer in different ways. In this review, we focus on recent advances in our understanding of the structure, function, and organization of the T9SS machinery and new findings about this highly novel secretion system in R. anatipestifer.